2019
DOI: 10.1111/jpy.12907
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light and temperature on the growth of Takayama helix (Dinophyceae): mixotrophy as a survival strategy against photoinhibition

Abstract: Takayama helix is a mixotrophic dinoflagellate that can feed on diverse algal prey. We explored the effects of light intensity and water temperature, two important physical factors, on its autotrophic and mixotrophic growth rates when fed on Alexandrium minutum CCMP1888. Both the autotrophic and mixotrophic growth rates and ingestion rates of T. helix on A. minutum were significantly affected by photon flux density. Positive growth rates of T. helix at 6–58 μmol photons · m−2 · s−1 were observed in both the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Higher temperature implies higher metabolic rates and concomitantly an increased need for energy, and possible stress incurrence. Studies have indeed shown higher ingestion rates in response to temperature increase in many species (Princiotta et al, 2016;Cabrerizo et al, 2019;Ok et al, 2019). This validates the applicability of the general theory of metabolism in marine protists.…”
Section: Temperaturesupporting
confidence: 76%
See 1 more Smart Citation
“…Higher temperature implies higher metabolic rates and concomitantly an increased need for energy, and possible stress incurrence. Studies have indeed shown higher ingestion rates in response to temperature increase in many species (Princiotta et al, 2016;Cabrerizo et al, 2019;Ok et al, 2019). This validates the applicability of the general theory of metabolism in marine protists.…”
Section: Temperaturesupporting
confidence: 76%
“…Karlodinium veneficum, and some other dinoflagellates, cannot grow (or are only sustained) in the dark even when prey is available, that is to say, it is an obligate phototroph. Other dinoflagellate species, or chrysophytes such as Ochromonas sp., can grow in constant darkness if supplied with food (Caron et al, 1993;Ok et al, 2019). Thus, predation can, but does not always, compensate for the inability to use chloroplasts in the dark.…”
Section: Lightmentioning
confidence: 99%
“…Temperature is a major factor affecting dinoflagellate survival, growth rate, and abundance (Hinder et al, 2012;Kohli et al, 2014;Ok et al, 2019;Jang and Jeong, 2020;You et al, 2020). In particular, many dinoflagellates cannot survive in very cold or hot waters (Matsubara et al, 2007;Kibler et al, 2012;Xu et al, 2016;Lim et al, 2019;Kang et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the amount of photons produced by a continuous light at 100 μmol photons m -2 s -1 is equivalent to that at 140 μmol photons m -2 s -1 under 14-h light : 10-h dark cycle. The autotrophic growth of the mixotrophic dinoflagellate Takayama helix is known to be inhibited at 115 μmol photons m -2 s -1 under 14-h light : 10-h dark cycle (Ok et al 2019). Therefore, it is worthwhile to explore possible inhibition of growth of A. fraterculus at high light intensities under 14-h light : 10-h dark cycle to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%